Outcomes after radiation therapy for T2N0/stage II glottic squamous cell carcinoma. Issue 10 (2nd June 2020) - Al Feghali, Karine A.; Youssef, Bassem Y.; Mohamed, Abdallah S. R.; Hilal, Lara; Smith, Blaine D.; Abu‐Gheida, Ibrahim; Farha, Georges; Gunn, G. Brandon; Phan, Jack; Lewin, Jan; Thekdi, Apurva; Morrison, William H.; et al.
Abstract: Background: We report outcomes for patients with T2N0M0 glottic squamous cell carcinoma (SCC) treated with radiation therapy (RT). Methods: Patients who received definitive RT for T2 glottic SCC from 2000 through 2013 were retrospectively reviewed. Results: One hundred and thirteen patients were analyzed (median follow‐up time 91 months; 85 patients received three‐dimensional conformal radiotherapy [3D‐CRT] and 28 received intensity‐modulated radiation therapy [IMRT]). Fractionation was conventional (58%) or altered (42%); 20 patients (18%) received concurrent chemotherapy. Five‐year local control was 83% for the 3D‐CRT vs 81% for the IMRT group ( P = .76). The ultimate locoregional control at 5 years was 100% for IMRT vs 91% for 3D‐CRT ( P = .1). The 5‐year overall survival (OS) was 78% for 3D‐CRT vs 81% for IMRT ( P = .83). On multivariate analysis, younger age was the only independent predictor of improved OS ( P = .0002). Conclusions: Oncologic and survival outcomes were excellent for patients with T2N0 glottic cancer. Patients treated with IMRT and 3D‐CRT had no statistically significant differences in all investigated endpoints.